(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 05:50:10
(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要
(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程
(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程
(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程
(a-b)(3a+b)^2+(a+3b)^2(b-a)
=(a-b)(3a+b)^2-(a+3b)^2(a-b)
=(a-b)[(3a+b)^2-(a+3b)^2]
=(a-b)[(3a+b)-(a+3b)] [(3a+b)+(a+3b)]
=(a-b)(3a+b-a-3b)(3a+b+a+3b)
=(a-b)(2a-2b)(4a+4b)
=8(a-b)(a-b)(a+b)
=8(a-b)^2(a+b)
(a-b)(3a+b)^2+(a+3b)^2(b-a)
(a-b)(3a+b)^2-(a+3b)^2(a-b)
(a-b)[(3a+b)^2-(a+3b)^2]
(a-b)(8a^2-8b^2)
8(a-b)(a^2-b^2)
8(a-b)(a+b)(a-b)
(a-b)(3a+b)²+(a+3b)²(b-a)
=(a-b)(3a+b)²-(a+3b)²(a-b)
=(a-b)[(3a+b)²-(a+3b)²]
=(a-b)[(3a+b)+(a+3b)][(3a+b)-(a-3b)]
=(a-b)(4a+4b)(2a+4b)
=8(a-b)(a+b)(a+2b)
(a-b)(3a+b)²+(a+3b)²(b-a)=(a-b)[(3a+b)²-(a+3b)²]=(a-b)[(3a+b)+(a+3b)][(3a+b)-(a+3b)]=(a-b)(4a+4b)(2a-2b)=8(a-b)²(a+b)
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
(2a-3b)[(a+b)-b(a-3b)]
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/a]
化简:[2/3a - 2/(a+b) * (a+b/3a - a - b)] / (a-b)/a
2(a+3b)²-8(a+b)(a-b)-(a+3b)(a-b)
a^2(a-b)+b^2(b-a) 因式分解 (a-b)^3-(a-b)^2 因式分解
A-B A+B 2B+A 3A-B 6A+2B
化简a/b(a-b)-b/a(a-b)其中a=3 b=-2
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
(a-b)(3a+b)^2+(a+3b)^2(b-a)因式分解要过程
[3(a+b)^4-1/2(a+b)-a-b]/(a+b)
2(a-b)²(a+b)-(b-a)²(3a-b)因式分解
2b²+(a+b)(a-b)-(a-b)²,其中a=-3
计算(a/a-b+b/b-a)/(1/a+b)的结果 (1)a-b (2)ab (3)a^2-b^2 (4)a+b
A=B+B+B+B+B+B+B+B+B+B+B+B+B+B+B A-B×3=C C+2×7+2=1A=B+B+B+B+B+B+B+B+B+B+B+B+B+B+BA-B×3=CC+2×7+2=148148-(C-32)=DA,B,C,D各是多少?
3(a+b)^2-(a+b)+2(a+b)^2-(a+b)^3+4(a+b)合并同类项